2006
DOI: 10.1007/s11425-004-5169-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic normality and strong consistency of maximum quasi-likelihood estimates in generalized linear models

Abstract: In a generalized linear model with q × 1 responses, the bounded and fixed (or adaptive) p × q regressors Z i and the general link function, under the most general assumption on the minimum eigenvalue of n i=1 Z i Z i , the moment condition on responses as weak as possible and the other mild regular conditions, we prove that the maximum quasi-likelihood estimates for the regression parameter vector are asymptotically normal and strongly consistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Remark Condition (C1) is common in MQLE, supi1false‖Xifalse‖< is necessary due to the nonlinearity of boldh (see Yin et al ., ), and λtrue̲n is a sufficient condition for the consistency of MQLE βtrue˜n (see Chen et al ., ). Conditions (C4) and (C5) are for the asymptotic normality of estimates with adaptive designs (see also Lai and Wei, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark Condition (C1) is common in MQLE, supi1false‖Xifalse‖< is necessary due to the nonlinearity of boldh (see Yin et al ., ), and λtrue̲n is a sufficient condition for the consistency of MQLE βtrue˜n (see Chen et al ., ). Conditions (C4) and (C5) are for the asymptotic normality of estimates with adaptive designs (see also Lai and Wei, ).…”
Section: Methodsmentioning
confidence: 99%
“…Under Conditions (C1)-(C3), Yin, Zhao and Wei (2006); Yin, Zhang and Zhao (2008) showed that the convergence rate of the MQLE βn is:…”
Section: Adaptive Shrinkage Estimatementioning
confidence: 99%
See 1 more Smart Citation
“…The ANN models employed in this study have a hidden layer with a sigmoid activation function, which is often used in biology for the characteristics of smoothness and ease of derivation. The application of the ANN models in the environment research field generally includes: estimating the reference evapotranspiration (ET0) in a river ecosystem [46], predicting the total phosphorus (TP) concentration in the overlying water of the Huai River based on hydrological and hydrodynamic parameters [47], predicting the total dissolved gas (TDG) downstream of spillways of dams [48], and predicting the algae distribution in the large shallow lake based on wind speed index [49]. However, there are few studies on the application of ANN to SD prediction.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…The moments condition ( 9) is crucial to explain the finite moments behavior of the exponential families. This condition means, in most cases, that there is a compact subset K, not depending on n, of the interior of Θ such that u( Yin et al (2006) for establishing the strongly consistent maximum quasi-likelihood estimates.…”
Section: Regularity Conditionsmentioning
confidence: 99%